Collaborative distributed design for wireless control systems with Markovian‐type control network and distributed network‐induced time delays - Wen, Jiwei; Nguang, Sing Kiong; Zhao, Xudong (International journal of robust and nonlinear control, 2018)
Summary In this paper, collaborative distributed dynamic output‐feedback control problem is investigated for a class of wireless control systems with Markovian‐type control network and distributed network‐induced delays. The network consists of a set of interconnected nodes characterized by a directed graph with an adjacency matrix that specifies space distribution (ie, interconnection topology). Each node of wireless control systems not only routes information but also performs its local control. We assume measurements and distributed network‐induced delays are subject to two independent Markovian chains. It is shown that the collaborative distributed dynamic output‐feedback approach offers better performances compared with noncollaborative distributed control approach. An irrigation canal system is used to demonstrate practical potentials of the developed control strategy.